Variation in the BRCA2 gene in a child with medulloblastoma and a family history of breast cancer - Bayrakli, Fatih; Akgun, Bekir; Soylemez, Burcak; Kaplan, Metin; Gurelik, Mustafa (Amer Assoc Neurological Surgeons, 2011)
The fact that BRCA genes operate as tumor suppressors is evident from the genetics of the different human disorders caused by inherited mutations. Germline mutations affecting 1 allele of either BRCA1 or BRCA2 confer susceptibility to different types of cancers such as breast cancer and medulloblastoma. A family with a history of cancer was identified in Eastern Turkey in which one of the family members (a 13-year-old boy) had medulloblastoma. Venous blood was collected from available family members. The BRCA1 and BRCA2 genes were sequenced in the patient with medulloblastoma and the healthy father. An Asn372His homozygous variation was noted in the BRCA2 gene in the patient with medulloblastoma whereas the variation was heterozygous in the healthy father. A biallelic homozygous variation was demonstrated in the BRCA2 gene, which is important in medulloblastoma suppression, and may have caused medulloblastoma formation in the 13-year-old boy. Further investigations in large human populations with medulloblastoma are necessary for further delineation of BRCA gene malfunctions and their relationship to medulloblastoma formation, and to clarify the therapeutic implications of these malfunctions. (DOI: 10.3171/2011.8.PEDS11210)
Keywords: medulloblastoma; BRCA1; BRCA2; breast cancer; oncology